A Protocol for the Prevention of Central Line Occlusion and Central Line-Associated Bloodstream Infection in Home Health - Holston, Felicia (My University, 2017)
Problem Statement: Central line-associated blood stream infection (CLABSI) is a significant healthcare acquired infection that is usually caused by inappropriate maintenance of central lines and leads to increased health costs, sepsis, and mortality. Purpose: The home health care setting has not been well researched for common central line complications, nor are there published evidence-based standardized protocols. The purpose of this project was to establish an evidence-based home healthcare protocol for the care of central lines targeting the prevention of the common central line complication of occlusion. Method: An evidence based protocol was designed and implemented at a home health agency in North Carolina, used by the clinical staff to prevent and/or treat clotted ports of central lines. The protocol included proper flushing techniques, troubleshooting steps, and thrombolytic treatment of clotted ports. Analysis: The first part of the analysis compared the retrospective number of clotted lines for three months prior to the implementation of the protocol to the number of clotted lines three months after implementation. The second part of the analysis reviewed how the protocol performed in the prevention of and resolution of clotted lines. Finally, input from the staff on the usability of the protocol and suggestions for refinement were obtained at the end of the implementation period. Significance: This project demonstrated that there was an improvement in the number of problems associated with line occlusion, there was appropriate treatment with a thrombolytic agent as stipulated in the protocol, and there were no delays in therapy related to improvements in line functionality.
Keywords: central line associated blood stream infection, central line, occlusion, home health care, central line guidelines